The ferroelectric PLZT type ceramics as a material for transducers - Czerwiec, Marek; Zachariasz, Radosław; Ilczuk, Jan (Archives of Acoustics, 2007)
Modification of the PZT system by the addition La$^{3+}$ ions has marked beneficial effect onseveral the basic parameters, such as squerness of the hysteresis loop, decreased coercive filed,increased dielectric constant, maximum coupling coefficients, increased mechanical compliance,and enhanced optical transparency.The mechanical and electrical properties in lanthanum modified lead zirconate-titanate ceramicsof 5/50/50 and 10/50/50 were studied by electric permittivity $ε$ and dielectric lossestan $δ$ measurements. The temperature dependences of $ε = f(T)$ and tan $δ = f(T)$ weredeterminate in temperature range from 300 K to 730 K. The values of $T_C$ obtained during $ε$and tan $δ$ measurements were respectively: 560 K for 5/50/50 and 419 K for 10/50/50.